How the world was won / Peter Conrad. - Conrad, Peter, 1948- (Thames & Hudson, 2014)
Cultural critic and historian Peter Conrad tells the story of the spectacular rise and subsequent waning of American influence across the world since 1945. Politics, war and commerce form the inevitable backdrop to his tale, but Conrad also treats us to a kaleidoscopic presentation of America's unstoppable creativity: its output of great, good and enjoyably bad art, of jeans and jazz, fast food and fridges, space travel, comic books and motorbikes, technologies and therapies, along with the heroic, erotic or violent cinematic visions that have Americanised even our dreams.